Exploring the gut microbiota of healthy captive Asian elephants from various locations in Yunnan, China - Wang, Yuhan; Wang, Yixuan; Zhou, Jiuxuan; Bao, Mingwei; Shah, Taif; Yang, Song; Zheng, Jing; Li, Qian; Hou, Yutong; Wang, Binghui; Yuan, Ruiling (Frontiers in Microbiology, 2024)
The Asian elephant (Elephas maximus) is a giant herbivore classified as an endangered wildlife species by the International Union for Conservation of Threatened Species. In this study, we investigated and compared the core microbiota in the guts of captive Asian elephants from three locations in Yunnan Province, China. Alpha diversity using Chao1 and Shannon diversity indexes quantifies microbial differences between groups, indicating that the microbial profiles in the YeXiangGu group were higher than the other groups. The Bray-Curtis and Euclidean distance metrics revealed significant differences among the microbial communities. Two principal coordinate analysis plots using the Bray-Curtis and Euclidean distance metrics visualized the percentage variations in the microbial profiles. These findings indicate that the visualized percentage of microbial variation may be attributed to differences in their habitats and husbandry factors.According to the relative abundance, phyla Bacteroidetes and Firmicutes, which mainly comprise cellulose-degrading bacteria that produce energy for the hosts, were higher in the guts of Asian elephants. The family-level classification shows Synergistaceae with the highest abundance in the MengHai group, followed by the YuanTongShan and YeXiangGu. In the YeXiangGu group, Lachnospiraceae was the richest, whereas Pirellulaceae was the highest in the YuanTongShan group. Genus p-1008-a5-gut-group was higher in YeXiangGu, whereas Prevotella was more abundant in the MengHai group, emphasizing the importance of certain bacterial taxa in maintaining host-microbial interactions. In addition, several bacterial species, including Lactobacillus fermentum, Clostridium neonatale, Enterococcus mundtii, Klebsiella huaxiensis, Corynebacterium nasicanis, Streptococcus equinus, etc., were identified in the guts of Asian elephants.These findings underscore the impact of environmental and husbandry factors on the gut microbiota of Asian elephants, highlighting the importance of animal captivity to promote microbial diversity for health benefits.